Detection of OmpA and blaPER-1 Genes and Biofilm Formation in Acinetobacter baumannii Clinical Isolates - Ban Abdulsattar; Rasha Jabbar; Susan Ibrahim (Al-Anbar Medical Journal)
Background: Multi-drug-resistant Acinetobacter baumannii (MDR A. baumannii) infections are an ongoing problem in many hospitals, particularly in intensive care units. One of the most difficult infections to treat is A. baumannii because it forms a biofilm.Objectives: To identify MDR A. baumannii biofilm producers from clinical isolates and detect some biofilm-related genes.Materials and methods: During the period from October 2023 to February 2024, a total of 26 A. baumannii clinical isolates were collected from the laboratory of Ghazi Al-Hariri Hospital, Baghdad, Iraq. The automated VITEK®2 system was used to identify A. baumannii isolates phenotypically. The blaOXA51 gene confirmed A. baumannii isolates genotypically. The microtiter plate test and scanning electron microscopy were performed to assess biofilm formation. The presence of the biofilm-forming genes OmpA and blaPER-1 was evaluated.Results: Overall, most of the specimens were from sputum (38.5%), and all the isolates were MDR with a high resistance percentage to imipenem at 100%, meropenem, ceftriaxone, and ciprofloxacin. The isolates showed 80.77% resistance to trimethoprim/sulfamethoxazole and 100% sensitivity to colistin. The results showed that among the 26 isolates, 31% were moderate biofilm formers, 54% were weak biofilm formers, and only 4 isolates were non-biofilm formers (15%). The occurrence rates of the biofilm-related genes OmpA and blaPER-1 were 16 (61.5%) and 1 (3.8%), respectively.Conclusion: The current study suggests the presence of MDR A. baumannii isolates harbouring the biofilm OmpA and blaPER-1 genes.